Glioma Cells With Genetically Engineered IGF-I Receptor Downregulation Can Persist in the Brain in a Dormant State - Samani, Amir A.; Nalbantoglu, Josephine; Brodt, Pnina (Frontiers in Oncology, 2020)
The median survival time for glioblastoma multiforme patients undergoing surgery and standard radiotherapy is less than one year, highlighting the need for alternative therapeutic approaches. Here, we assessed the ability of a retroviral vector expressing type 1 insulin like growth factor receptor (IGF-IR) antisense RNA to inhibit the intra-cerebral growth of human and rat glioma cells. We produced a pseudotyped retrovirus expressing an IGF-IR antisense RNA, (vLTR-IGF-IRAS). Human U87 MG-LacZ and rat C6-LacZ glioma cells were transduced with the vLTR-IGF-IRAS retroparticles either prior to, or following the orthotopic, intra-cerebral injection of the cells. The effects of the retroparticles on tumor growth and on long-term animal survival were then evaluated. Ex-vivo transduction of rat C6 cells with vLTR-IGF-IRAS prior to intra-cerebral implantation caused a significant increase in the proportion of apoptotic cells in vivo, relative to controls and a marked reduction in tumor volumes as measured on day 24 post injection (p<0.0015). This resulted in a significant increase in long-term survival with more than 70% of the rats still alive 182 days post tumor inoculation (p<0.01). Interestingly, analysis of brain tissue obtained from surviving, healthy animals 182 days post inoculation revealed the presence of multiple, widely disseminated, solitary cells that retained the expression of a β-galactosidase marker protein, but were Ki67-negative, consistent with the acquisition of a growth-arrested (dormant) phenotype. Moreover, in vivo injection of the retroviral particles into pre-implanted C6 glioma tumors growing in the brain was also effective in blocking tumor growth, reducing tumor volumes by 22% relative to controls (p<0.026). A marked anti-tumorigenic effect was also observed with vLTR-IGF-IRAS- transduced human U87 glioma cells implanted orthotopically into athymic nude mice. Tumor volumes in animals implanted with these cells were significantly reduced, relative to controls, and this led to a significant increase in long-term survival, with 70% of the animals still alive at 6 months post injection. Our data provide proof of concept data for the utility of intra-cerebral IGF-I receptor targeting for the treatment of glioma and raise a note of caution regarding the ultimate fate of the transduced cells.